Analysis Of Factors Influencing Purchasing Decisions On The Shopee Marketplace - Yopi; Sihombing, Jonmaianto (Riset Sinergi Indonesia, 2025)
In today's digital era, the majority of consumers tend to prefer online shopping, with platforms like Shopee becoming increasingly popular. The convenience and ease offered by such e-commerce services are key reasons behind the growing interest in online purchases. Shopee, in particular, provides security features that enhance customer confidence, such as the ability to receive a refund if the seller fails to deliver the purchased item. Additionally, buyers can track their orders through shipment tracking numbers provided by the seller, which helps estimate delivery times. These user-friendly features significantly influence consumer behavior and purchasing decisions. This study aims to examine the extent to which factors such as product quality, price, and marketing strategies contribute to consumers' buying intentions. Furthermore, it explores the relationship between product quality, cost, and consumers' purchasing choices. Understanding these interconnections is essential for business owners and marketers in order to refine their strategies and remain competitive in the increasingly crowded digital marketplace. By analyzing these aspects, the study provides insights into how businesses can better meet consumer expectations and influence purchase decisions effectively in an environment where convenience, trust, and perceived value are critical